British crime survey experimental data: children aged 10-15 years, January-December, 2009 (Crime Survey for England and Wales, 2020)
The Crime Survey for England and Wales (CSEW) asks a sole adult, in a random sample of households, about their, or their household's, experience of crime victimisation in the previous 12 months. These are recorded in the victim form data file (VF). A wide range of questions are then asked covering demographics and crime-related subjects such as attitudes to the police and the criminal justice system (CJS) these variables are contained within the non-victim form (NVF) data file. In 2009, the survey was extended to children aged 10-15 years old; one resident of that age range is also selected from the household and asked about their experience of crime, and other related topics. The first set of children's data covered January-December 2009 and is held separately under SN 6601. From 2009-2010, the children's data cover the same period as the adult data and are included with the main study.